Monophasic-Quadripulse Theta Burst Magnetic Stimulation for Motor Palsy Functional Evaluation After Intracerebral Hemorrhage - Fujiki, Minoru; Matsushita, Wataru; Kawasaki, Yukari; Fudaba, Hirotaka (Frontiers in Integrative Neuroscience, 2022)
Transcranial magnetic stimulation (TMS) is commonly employed for diagnostic and therapeutic purposes to enhance recovery following brain injury, such as stroke or intracerebral hemorrhage (ICH). Single-pulse TMS, most commonly used for diagnostic purposes and with motor evoked potential (MEP) recordings, is not suitable for clinical use in patients with severe motor paresis. To overcome this problem, we developed a quadripulse theta burst transcranial magnetic stimulation (QTS) device that combines the output from 16 stimulators to deliver a train of 16 monophasic magnetic pulses through a single coil. High-frequency theta rhythm magnetic bursts (bursts of four monophasic pulses, at 500 Hz, i.e., with a 2-ms interpulse interval, repeated at 5 Hz) were generated via a set of 16 separate magnetic stimulators connected to a specially designed combination module. No adverse effects or electroencephalogram (EEGs) abnormalities were identified during or after the recordings. MEP amplification in the QTS during four-burst theta rhythm stimulations produced four independent MEPs 20 ms after each burst onset maximizing the final third or fourth burst, which exhibited significantly greater amplitude than those resulting from a single burst or pulse. Motor functional palsy grades after ICH and QTS-MEP parameters and resting motor threshold (RMT) and amplitudes were significantly correlated (r = −0.83/−0.81 and 0.89/0.87; R2 = 0.69/0.66 and 0.79/0.76, p < 0.001; anterior/posterior-stimulus polarity, respectively). In conclusion, QTS-MEPs enabled a linear functional evaluation in patients with various degrees of motor paresis. However, the benefits, safety, and limitations of this device should be further explored in future studies.